Lightweight Robotic Joint with Thermally Activated Paraffin Actuator in the Deep Sea - Dayong Ning; Xiaokang He; Jiaoyi Hou; Gangda Liang; Kang Zhang (Journal of Marine Science and Engineering, 2023)
The abundance of resources in the deep sea continues to inspire mankind’s desire for exploration. However, the extreme environments pose a huge challenge for designing deep-sea mechanical devices that are primarily driven by hydraulic and electric motor technology. Researchers are beginning to explore more flexible and innovative drive methods suitable for the deep-sea environment. This paper presents a simple joint mechanism based on a paraffin phase change thermal expansion drive. Its unique design combines a flexible cell with an open structure that allows it to adapt to different pressures at different water depths. Paraffin is enclosed in multiple sets of smaller paraffin cells, which act as thermal expansion material for generating hydraulic pressure. The software comsol was used to perform a finite element analysis of the phase change process in paraffin. By fabricating the mechanical structure, the displacement generated by the thermal expansion is amplified and converted, thus enabling a bi-directional rotational displacement output from the joint while reducing the complexity of the structure. The joints in this paper provide a reliable reference for the design of small deep-sea robot drive systems.